Examining elements of social injustice in females' science education in schools : a case study - Hallab, Rula (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2006)
The purpose of this study was to explore factors that discouraged female students from choosing the scientific academic track at the secondary level in a private school with two branches in Lebanon. This was done through examining the role of schools, parents and society in addition to other factors that contributed to females' gender inequity in education. The sample consisted of al l female students of grade 10 and the science and mathematics teachers of the same grade level. The instruments that were used were closed-itemed female students' questionnaires, semi-structured science and mathematics teachers' interviews as well as parents' phone interviews and observations of teacher student- interactions in science and mathematics classes. The results showed discrepancies between what students and teachers said about gender equity and practices in classrooms and the strong gender bias in Lebanese Baccalaureate science and mathematics textbooks that students were exposed to. Results also indicated that teachers were not aware of their hidden biased beliefs. In other words, gender inequity existed in this school due to discouraging factors such as teachers' attitudes, parents' socialization, gender bias in textbooks and female students' lack of self-confidence. On the other hand, female students ' abilities and achievements and the diminishing influence of social stereotypes on their attitude toward science were promising factors that might give hope for a brighter future.
: Mémoire
Keywords: Gender; L enseignement des Sciences; Sciences education; Sexe Justice sociale; Social Justice